1983
DOI: 10.1128/aac.24.4.486
|View full text |Cite
|
Sign up to set email alerts
|

Agar disk elution method for susceptibility testing of Mycobacterium marinum and Mycobacterium fortuitum complex to sulfonamides and antibiotics

Abstract: An agar disk elution method using round well plates, supplemented MuellerHinton agar, and commercial drug disks is described for susceptibility testing of Mycobacterium marinum and the rapidly growing mycobacteria to antibiotics and sulfonamides. By this method, 14 of 14 strains of M. marinum were susceptible to rifampin, doxycycline, minocycline, and trimethoprim-sulfamethoxazole. Identical results were obtained with Middlebrook 7H10 agar and drugs prepared from standard powders. With 58 isolates of Mycobacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…In some studies, the methods used were those designed for slowly growing mycobacteria, such as the proportion method on solid media and in BACTEC liquid media (10). In contrast, in other studies, the methods used for antibiotic susceptibility testing of M. marinum were those designed for rapidly growing mycobacteria, such as broth microdilution (14), disk diffusion, agar disk elution (22), or agar dilution using a Steers replicator (20,25). M. marinum grows rapidly enough, indeed, to be tested by the method used for rapidly growing mycobacteria, despite the fact that it belongs to the slowly growing mycobacteria on the basis on genetic and mycolic acid analysis (5,21).…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, the methods used were those designed for slowly growing mycobacteria, such as the proportion method on solid media and in BACTEC liquid media (10). In contrast, in other studies, the methods used for antibiotic susceptibility testing of M. marinum were those designed for rapidly growing mycobacteria, such as broth microdilution (14), disk diffusion, agar disk elution (22), or agar dilution using a Steers replicator (20,25). M. marinum grows rapidly enough, indeed, to be tested by the method used for rapidly growing mycobacteria, despite the fact that it belongs to the slowly growing mycobacteria on the basis on genetic and mycolic acid analysis (5,21).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that agar and broth microdilution methods work well when applied to M. fortuitum and M. chelonae (19) and that antimicrobial agents other than antituberculosis agents should be tested. However, we do prefer the broth test because M. chelonae grows better in broth than on agar, especially if no supplements such as oleic acid-albumin-glucose (dextrose)-catalase are added (OADC) (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Susceptibility testing is then performed by applying the method of proportions with a inoculum that averages 100 to 400 CFU/ml (167). The advantages of this method are that it utilizes materials and commercial drug disks readily available in most susceptibility laboratories and that the plates may be prepared on demand.…”
Section: Susceptibility Testing For Clinical Purposesmentioning
confidence: 99%